TEKNIK PENGAJARAN TATA BAHASA ARAB DENGAN MEDIA KARTU KATA GUNA MEMBERIKAN PEMAHAMAN TENTANG QOWA’ID KEPADA PESERTA DIDIK - Roisatul Mu'awwanah; Anin Nurhayati; Luk- Luk Nur Mufidah (Irsyaduna: Jurnal Studi Kemahasiswaaan, 2022)
Arabic language learning is the learning of foreign languages that has been taught in schools. To be able to read and write and translate Arabic writing, it requires an adequate mastery of nahwu and shorof knowledge. The obstacle experienced by students so far is the difficulty of formulating nahwu shorof in an easy way of learning. Judging from these problems, teachers should have developed learning strategies. Which in the learning strategy includes learning methods and techniques, which function so that learning in the classroom can run more effectively and efficiently. In other words, learning techniques are certain activities carried out in the classroom in accordance with the strategies and methods chosen that are in accordance with the approach to the existing problems. In this article, we will discuss grammar learning techniques (qowaid) to make it easier for students to understand nahwu and shorof material.